PHILOSOPHICAL TAFSIR: A Rational Approach to Interpreting the Qur'an: TAFSIR FALSAFI: Pendekatan Rasional dalam Penafsiran Al-Quran - Abdul Gofur; R. Muhammad Farhal Azkiya; Eni Zulaiha (Senarai: Journal of Islamic Heritage and Civilization, 2025)
This article discusses the interpretation of the Quran using a philosophical approach, reflecting the interaction between religious teachings and philosophical thought. This interpretation is rooted in the historical development of science and Islamic culture, especially during the Abbasid caliphate. Through analysis of definitions, boundaries, and scholarly debates regarding philosophical exegesis, the article identifies distinctive features such as a logical approach, integration with philosophy, the use of philosophical terminology, and an emphasis on cosmological and metaphysical verses. Additionally, the article evaluates the advantages, such as deep understanding and contributions to knowledge, as well as the disadvantages, including potential negative impacts on Islamic creed. Thus, philosophical interpretation offers a rich perspective but must be conducted carefully to avoid straying from fundamental religious principles.